Industrial and intellectual property: Patent protection for medicines and international trade - Romero Matute, Yeray (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
As a consequence of technological progress and the elimination of obstacles to international trade, there has always been a certain concern when adopting regulations to ensure the protection of industrial and intellectual property rights. It is for this reason that obtaining a patent and the exclusive right to exploit it entails the need to ensure that this “right” is valid in a given country. From the point of view of private international law, and given that it is the inherent rights associated with certain intangible products that are to be protected, the determination of a court, as well as the determination of the applicable law, are crucial aspects when it comes to protecting these rights.